Identification of a gene responsible for seedpod spine formation and other phenotypic alterations using whole-genome sequencing analysis in Medicago truncatula - Zhao, Zhili (Journal of experimental botany, 2021)
© The Author(s) 2021. Published by Oxford University Press on behalf of the Society for Experimental Biology. All rights reserved. For permissions, please email: journals.permissionsoup.com.